A Vajdasági Római katolikus templomok architektúrája 1699-1939 / Architecture of Roman Catholic Churches in Vojvodina from 1699 to 1939 / Dubravka Đukanović - Karač, Zlatko (Arhitektura i urbanizam, 2022)
A synthetic scientific monograph on the Roman Catholic Churches of Vojvodina, built from 1699 to 1939, was published in Hungarian and English in 2019 as a joint venture of three eminent publishers. The focus of the research is a significant corpus of built heritage of 243 sacral buildings that represent an important identity determinant of the multiethnic and multi-confessional cultural landscape of Vojvodina. In addition to the results of a comprehensive stylistic and typological analysis of the studied buildings the interpretation of the origin, characteristics, periodization, and origins of certain architectural types through the explanation of the flows and strengths of architectural influences, is the special value of this monumental work. This contextualized analysis connects the space and heritage of Vojvodina with the wider Central European cultural circle.